2014
DOI: 10.1038/ng.3066
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of NLRC4 causes a syndrome of enterocolitis and autoinflammation

Abstract: Upon detection of pathogen-associated molecular patterns, innate immune receptors initiate inflammatory responses. These receptors include cytoplasmic NOD-like receptors (NLRs), whose stimulation recruits and proteolytically activates caspase-1 within the inflammasome, a multi-protein complex. Caspase-1 mediates the production of interleukin-1 family cytokines (IL1FCs), leading to fever, and inflammatory cell death (pyroptosis)1,2. Mutations that constitutively activate these pathways underlie several autoinfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
391
3
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 455 publications
(413 citation statements)
references
References 28 publications
6
391
3
13
Order By: Relevance
“…Recently, activating mutations in the gene coding for another NLR, NLRC4, have been associated with an autoinflammatory disease that differs from CAPS [52,53]. Patients with these NLRC4 mutations exhibited early-onset spontaneous fevers, gastrointestinal (GI) inflammation, urticaria, splenomegaly and malaise.…”
Section: Autoinflamamatory Diseases Linked To Disorders In Protein MImentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, activating mutations in the gene coding for another NLR, NLRC4, have been associated with an autoinflammatory disease that differs from CAPS [52,53]. Patients with these NLRC4 mutations exhibited early-onset spontaneous fevers, gastrointestinal (GI) inflammation, urticaria, splenomegaly and malaise.…”
Section: Autoinflamamatory Diseases Linked To Disorders In Protein MImentioning
confidence: 99%
“…In contrast to CAPS but like MAS, monocytes and macrophages with the NLRC4 mutations showed hypersecretion of IL-18 [52]. Romberg et al showed that NLRC4 mutant macrophages also exhibited increased apoptosis [53].…”
Section: Autoinflamamatory Diseases Linked To Disorders In Protein MImentioning
confidence: 99%
“…5). V341A and T337S patients had very high serum IL-18 levels compared to healthy volunteers or CAPS patients [72,73].…”
Section: Nlrp3 Is Recruited To the Same Complex As Phosphorylation Dementioning
confidence: 99%
“…The V341A mutation causes severe inflammatory phenotype in humans, with neonatal-onset enterocolitis [72], while T337S mutation leads to early-onset recurrent fever flares and macrophage activation syndrome [73]. These mutants are active in the absence of known NLRC4 activators (Fig.…”
Section: Nlrp3 Is Recruited To the Same Complex As Phosphorylation Dementioning
confidence: 99%
“…A matching receptor surface is preformed in the inactive NLRC4 molecule, and mediates the recruitment of NLRC4 into the growing complex. Intriguingly, missense mutations in NLRC4 that are associated with autoinflammatory conditions map to this important hinge region [7][8][9]. Whether such mutations induce the formation of NLRC4 disks in the absence of activated NAIPs remains to be shown, but the new studies provide the structural basis for understanding these gain-of-function mutations.…”
mentioning
confidence: 99%